Tuning Organic Room‐Temperature Phosphorescence through the Confinement Effect of Inorganic Micro/Nanostructures. Issue 9 (20th July 2021) - Huang, Qiuqin; Lin, Zhenghuan; Yan, Dongpeng
Abstract : Organic room‐temperature phosphorescence (RTP), especially ultralong organic RTP (UOP), has great application potential in emerging fields, such as flexible intelligent information encryption, optical anticounterfeiting, and biological imaging. Therefore, the studies on organic RTP and UOP have attracted extensive attention in recent years. Various strategies, such as crystallization, host–guest interactions, spatial confinement, and introducing weak forces of heteroatoms, have been used to improve phosphorescence quantum yield and lifetime. Among them, the confinement effect of inorganic micro/nanostructures can effectively promote highly stable and tunable organic RTP and UOP. Both the efficiency and lifetime of RTP for organic phosphors within inorganic micro/nanostructures can be improved by the confinement of inorganic frameworks, together with interactions between organic and inorganic components. Herein, the recent progress in the RTP and UOP of organic molecules assembled in micro/nanostructures of organic/inorganic hybrid materials is summarized, including low‐dimensional metal halides, metal−organic frameworks with ordered nanochannels, silica nanocomposites with micro/nanopores, and layered nanoclays. In particular, the characteristics of each hybrid structure which are beneficial for RTP are highlighted. Finally, future directions of each hybrid material are suggested to continue to expand this area of research. Abstract : Molecular materials with room‐temperature phosphorescence (RTP) have recently drawn great attention. The confinement effect of inorganic micro/nanostructures can effectively improve the phosphorescence efficiency and lifetime of organic molecules. Herein, the recent progress in the organic RTP from the views of fabricating state‐of‐the‐art micro/nanomaterials is reviewed, including low‐dimensional metal halides, metal−organic framework, silica nanocomposites, and layered clays.